(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The most promising 3 wild-growing species Tulipa Ostrowskiana Regel, Tulipa Kolpakowskiana and Tulipa tarda Stapf and 7 varieties of tulips Jumbo Pink, Sinaeda King, Shirley Double, Wild Tulipen Saxatilis, Monsella, Salmon Prince introduced in the Main Botanical Garden are promising for landscaping in the South-East of Kazakhstan. Currently, the problem of landscaping is one of the urgent problems. In this regard, tulips are promising for creating spring-flowering flower beds in the cities of Kazakhstan. Their diversity in color of the flower and the height of the peduncles allows you to create bright, spectacular groups on the streets of the city.